Iowa Birdline update, January 14, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for January 14, 1991. Highlights include two Snowy Owl reports, a Varied Thrush and Red Crossbills. Epson - sheet feed/flatbed